Changement De Couverture Forestière Dans Le Département De La Likouala (République Du Congo) Durant La Période De 1986 À 2015 - Bouetou-Kadilamio, Leslie; Ifo, Suspense Averti; Binsangou, Stoffenne (European Scientific Journal, ESJ, 2017)
A study on the change of forest cover was carried out in the Department of Likouala, Republic of Congo for the period from 1986 to 2015. It was intended to calculate the areas of the different land conversions in the study period, but also to identify the causes of deforestation and forest land Landsat TM (1986), Etm + (2001), and Oli (2015) images were treated with the method of supervised classification "Maximum Likelihood" was applied to obtain the different maps of land type. The results revealed the lost of forest, with 133.624 hectares of intact forests in1986, 126980.89 ha of intact forests in 2001 and 114.166 ha of intact forests in 2015. There were also increases and regressions in areas of other types of land tenure. This study shows that agriculture is the main driving force for the conversion of forest land to non-forest land. Given the importance of the coverage of lost forests, it appears urgent to strengthen the sustainable management of these ecosystems with a view to combating climate change.